Single cell genomics of uncultured marine alveolates shows paraphyly of basal dinoflagellates - Strassert, Jürgen F H; Karnkowska, Anna; Hehenberger, Elisabeth; Del Campo, Javier; Kolisko, Martin; Okamoto, Noriko; Burki, Fabien; Janouškovec, Jan; Poirier, Camille; Leonard, Guy; Hallam, Steven J; Richards, Thomas A; et al. (The ISME journal, 2018)
Marine alveolates (MALVs) are diverse and widespread early-branching dinoflagellates, but most knowledge of the group comes from a few cultured species that are generally not abundant in natural samples, or from diversity analyses of PCR-based environmental SSU rRNA gene sequences. To more broadly examine MALV genomes, we generated single cell genome sequences from seven individually isolated cells. Genes expected of heterotrophic eukaryotes were found, with interesting exceptions like presence of proteorhodopsin and vacuolar H+-pyrophosphatase. Phylogenetic analysis of concatenated SSU and LSU rRNA gene sequences provided strong support for the paraphyly of MALV lineages. Dinoflagellate viral nucleoproteins were found only in MALV groups that branched as sister to dinokaryotes. Our findings indicate that multiple independent origins of several characteristics early in dinoflagellate evolution, such as a parasitic life style, underlie the environmental diversity of MALVs, and suggest they have more varied trophic modes than previously thought.
Keywords: Phylogeny; Single-Cell Analysis; Dinoflagellata; geny rRNA; analýza jednotlivých buněk; Genes, rRNA; Genomics; fylogeneze; Dinoflagellida; genomika